Apropriações de Bruno Latour pela Ciência da Informação no Brasil: descrição, explicação e interpretação - Ronaldo Ferreira de Araujo (2009)
Building on the theoretical framework within Science and Technology Studies (STS) provided by contemporary French philosopher Bruno Latour, this thesis aims at bringing some insight to the epistemological thinking of the Information Science (IS). Such a framework conceives of science as a social construction subject to interests, conflicts and contradictions, common to any other social activity. More specifically,the aim is to identify the major characteristics of these approaches, as well as their constructs, paths, concepts and related terms, by connecting them with the IS principles, namely: object of study, interdisciplinary matters, epistemological setting and human-technology relationship. To achieve this goal, this thesis consists of an exploratory study scrutinizing central issues for the Information Science and analyzing texts by Bruno Latour as well as papers citing this author published in ISspecificjournals. The empirical universe comprises 43 papers from 10 IS-specific journals issued from 1995 through 2007. The analysis shows that 34.88% of the papers fall into the topic theoretical and general aspects of the information science. The triangulation of methodologies (citation analysis, content analysis, and interpretative analysis) to approach the abovementioned papers yielded data on Latours quoted papers, on the reasons for citation of his work and related theoreticalframework as well as on the way the authors resort to Latours work. Although Latours work is remarkably present within the Information Science and highly potential for the information studies, it is hard to measure his influence upon or his contribution to the field, since the authors have not resorted to his work in a very clearly unambiguous, contextualized fashion. In conclusion, Bruno Latour offers a promising (re)construction path and yields productive discussions to the InformationScience, which is likely to be a fruitful way to consolidate and strengthen the field in terms of content and production context.